The Borzoi anthology of Latin American literature - Rodríguez Monegal, Emir; Colchie, Thomas (Alfred A. Knopf, Inc., 1977)
A comprehensive anthology including historical and critical as well as biographical commentary on each writer's work and on each major period in the literature as a whole.